Antistatic polyester fiber with conductivity and microporous structure and preparation method thereof
By adding conductive dispersions of montmorillonite, polyaniline and polypyrrole in the synthesis stage of polyester fibers and using pore-forming materials, the problems of high cost and complex process of traditional antistatic polyester fiber preparation methods are solved, and high efficiency is achieved , low-cost electrical conductivity and anti-static effect improve.
Patent Information
- Application Number
- CN202411528623.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The traditional antistatic polyester fiber preparation method is costly and complex, making it difficult to meet actual production needs.
When the esterification rate reaches more than 85% during the polyester synthesis stage, the conductive dispersion containing montmorillonite, polyaniline and polypyrrole is added, and the pore-forming material is added during the synthesis process, and then the polyester is made by melt spinning technology The fibers are removed and the pore-forming material is obtained to obtain anti-static polyester fibers with conductive and microporous structures.
The conductivity and antistatic effect of polyester fibers are significantly improved, while the hygroscopicity and breathability of the fibers are improved, and the process is simple and the cost is low.
Smart Images

Figure CN119392402A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, and in particular to an antistatic polyester fiber with electrical conductivity and a microporous structure and a preparation method thereof. Background Art
[0002] In textile production, static electricity has always been a serious challenge, especially in the production of polyester fibers such as polyester. The traditional way to eliminate static electricity is to add conductive agents to polyester fibers or their textiles, but this method is not only costly, but may also affect the mechanical properties, dyeing properties, and wearing properties of textiles, restricting the development of polyester-based textiles.
[0003] In view of the shortcomings of polyester fibers, some researchers have improved the antistatic effect of polyester fibers by modifying them in the synthesis stage. For example, the patent with publication number CN106380585A provides a method for preparing an antistatic copolyester, which prepares modified ethylene glycol I by mixing and grinding fluoride-modified lithium manganate, lithium iron phosphate nanopowder, sodium germanate, sodium bentonite with ethylene glycol, p-hydroxybenzoic acid, and butanediol; mixing and grinding silane coupling agent-modified tin oxide whiskers, conductive potassium titanate whiskers with polyethylene glycol, sodium bis(hydroxyethyl)isophthalate-5-sulfonate, ethylene glycol antimony, antioxidant, and ethylene glycol to prepare modified ethylene glycol II; then blending and beating modified ethylene glycol I with ethylene glycol and terephthalic acid for esterification reaction, adding modified ethylene glycol II in the normal pressure esterification-polycondensation stage, and further polycondensing to prepare antistatic copolyester, thereby improving the antistatic property, hygroscopicity, and mechanical properties of polyester materials. However, this patent requires the addition of a large amount of modifiers, the raw material cost is high, and the overall preparation process is relatively complicated, which is difficult to meet the needs of actual production.
[0004] In view of this, it is necessary to provide an improved method for preparing antistatic polyester fiber to solve the above problems. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides an antistatic polyester fiber with conductivity and microporous structure and a preparation method thereof, aiming to effectively improve the conductivity and antistatic effect of the polyester fiber in a simple way and at a low cost to meet the needs of actual production and application.
[0006] In a first aspect, the present invention provides a method for preparing an antistatic polyester fiber having conductivity and a microporous structure, comprising the following steps:
[0007] S1. preparing a conductive additive comprising montmorillonite, polyaniline and polypyrrole;
[0008] S2. dispersing the conductive aid in ethylene glycol to obtain a conductive dispersion;
[0009] S3. Synthesizing the copolyester by direct esterification, adding the conductive dispersion when the esterification rate reaches 85% or more, and then adding the pore-forming material, and after the polycondensation reaction is completed, obtaining a polyester product;
[0010] S4. The polyester product is made into polyester fiber by melt spinning technology, and the pore-forming material in the polyester fiber is removed to obtain an antistatic polyester fiber with conductivity and microporous structure.
[0011] In the technical solution of the embodiment of the present application, by adding a conductive dispersion containing montmorillonite, polyaniline and polypyrrole when the esterification rate reaches 85% or more in the polyester synthesis stage, the conductive dispersion can be blended and embedded into the polyester chain, thereby effectively improving the conductivity and antistatic effect of the polyester fiber, and the effect has high stability and is not affected by the washing, dyeing and other treatments of the polyester fiber. At the same time, by adding a pore-forming material in the synthesis process of the polyester and removing it after the polyester fiber is made, the embodiment of the present application can form grooves or pores in the polyester fiber, increase the specific surface area of the polyester fiber, and be more conducive to absorbing moisture and diffusing gas, thereby giving the polyester fiber better hygroscopicity and air permeability, and the improvement of the hygroscopicity of the polyester fiber can also further improve its antistatic effect.
[0012] In some embodiments, in step S1, the method for preparing the conductive additive comprises the following steps:
[0013] S11. The polypyrrole and the protonic acid are blended and dispersed in water, and then montmorillonite is added and stirred to obtain a montmorillonite dispersion;
[0014] S12. The polypyrrole and the oxidant are blended and dispersed in water to obtain a first mixed solution; the first mixed solution is added to the montmorillonite dispersion to obtain a second mixed solution;
[0015] S13. Adding the aniline suspension into the second mixed solution, after sufficient reaction, washing and drying the product to obtain the conductive additive.
[0016] In this embodiment, through the above steps, the polyaniline generated after the polymerization of polypyrrole and aniline can be distributed on the surface and interlayer of montmorillonite, the interlayer distance of montmorillonite is increased, and the dispersibility of montmorillonite in polyester is improved. On this basis, the conductive auxiliary agent formed is added to the synthesis process of polyester, which can effectively solve the problem that it is difficult to evenly disperse when directly adding polyaniline and polypyrrole, so that polyaniline and polypyrrole are evenly dispersed in polyester with montmorillonite, forming a continuous conductive network, and significantly improving the conductivity of polyester. At the same time, the synergistic effect of polyaniline and polypyrrole not only enhances the electronic transmission ability of the material, but also improves its stability under different conditions. In addition, the addition of montmorillonite can not only enhance the connectivity of the conductive network by improving the dispersibility of polyaniline and polypyrrole, but also itself can reduce the resistance of polyester to a certain extent, and improve the hygroscopicity and mechanical properties of polyester fiber. At the same time, due to the physical barrier effect of the interlayer space of montmorillonite, the growth of bacteria can be effectively inhibited, and the antibacterial properties of polyester fiber can also be improved.
[0017] In some embodiments, when preparing the conductive aid, the molar ratio of polypyrrole, protonic acid, montmorillonite, oxidant, and aniline used is 6:1:0.1-0.3:0.5:2; the mass ratio of polypyrrole used in step S11 and step S12 is 2:1.
[0018] In this embodiment, by adjusting the ratio of each raw material, aniline can be polymerized to generate polyaniline, and the synergistic effect among montmorillonite, polypyrrole and polyaniline can be fully utilized to improve the performance of the polyester fiber.
[0019] In some embodiments, the protonic acid includes at least one of hydrochloric acid, sulfuric acid, sulfosalicylic acid, and dodecylbenzenesulfonic acid, and the oxidant includes at least one of ammonium persulfate, potassium persulfate, ferric chloride, ferric sulfate, and ferric chloride.
[0020] In this embodiment, the montmorillonite can be pretreated by introducing the above-mentioned protonic acid, and the above-mentioned oxidant is used to promote aniline to generate polyaniline through chemical oxidation polymerization.
[0021] In some embodiments, in step S2, the mass fraction of the conductive additive in the conductive dispersion is 25% to 35%.
[0022] In this embodiment, the conductive auxiliary agent can be fully dispersed in ethylene glycol, so as to be fully dispersed in the polyester during the synthesis process of the polyester.
[0023] In some embodiments, in step S3, the step of synthesizing the copolyester comprises:
[0024] Mix terephthalic acid and ethylene glycol and carry out esterification reaction at 220-265°C;
[0025] Ethylene glycol was added to reduce the temperature, and then sodium bis(hydroxyethyl)isophthalate-5-sulfonate and polyethylene glycol were added.
[0026] In this embodiment, by introducing sodium bis(hydroxyethyl)-5-sulfonate isophthalate, hydrophilic sulfonic acid groups can be grafted into the polyester molecular chain, thereby increasing the moisture absorption rate of the fiber and further reducing the risk of static electricity accumulation.
[0027] In some embodiments, the mass of the conductive dispersion added in step S3 accounts for 10% to 20% of the mass of the terephthalic acid.
[0028] In this embodiment, by controlling the amount of conductive dispersion added, the proportion of the conductive additive in the polyester fiber can be effectively regulated, and polyester fibers with excellent conductivity, moisture absorption, antistatic effects and mechanical properties can be obtained at a relatively low cost to meet the needs of practical applications.
[0029] In some embodiments, the mass of the pore-forming material added in step S3 accounts for 8% to 15% of the mass of the terephthalic acid; the pore-forming material includes at least one of calcium carbonate and sodium chloride.
[0030] In this embodiment, by adjusting the proportion of the pore-forming material, the proportion of the microporous structure in the polyester fiber can be effectively adjusted.
[0031] In some embodiments, in step S4, the step of removing the pore-forming material comprises:
[0032] The polyester fiber is immersed in a solvent, and the polyester fiber is taken out after the pore-forming material is fully dissolved; the solvent is water or an acidic solution.
[0033] In this embodiment, by removing the pore-forming material, microporous structures such as grooves or small holes can be formed in the polyester fiber, thereby improving the moisture absorption and air permeability of the polyester fiber.
[0034] In a second aspect, an embodiment of the present application provides an antistatic polyester fiber having conductivity and a microporous structure, wherein the antistatic polyester fiber is prepared by the preparation method provided by any one of the above technical solutions.
[0035] In the technical solution of the embodiment of the present application, the antistatic polyester prepared by the above method has relatively stable conductivity and microporous structure, and its water absorption performance is comparable to that of natural fiber boxes. The textiles made of this polyester fiber have the characteristics of being dry and natural when in contact with the skin, and have excellent performance in moisture absorption, breathability and conductivity, and have excellent fluffiness and drape, which can effectively improve wearing comfort.
[0036] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 This is a SEM image of the antistatic polyester fiber with conductivity and microporous structure prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0039] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0041] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0042] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0043] In view of the problems in the prior art that polyester fibers have poor antistatic effects and conventional modification methods are too complicated or have poor effects, the present application provides an antistatic polyester fiber with conductivity and microporous structure and a preparation method thereof, comprising the following steps:
[0044] S1. preparing a conductive additive comprising montmorillonite, polyaniline and polypyrrole;
[0045] S2. dispersing the conductive aid in ethylene glycol to obtain a conductive dispersion;
[0046] S3. Synthesizing the copolyester by direct esterification, adding the conductive dispersion when the esterification rate reaches 85% or more, and then adding the pore-forming material, and after the polycondensation reaction is completed, obtaining a polyester product;
[0047] S4. The polyester product is made into polyester fiber by melt spinning technology, and the pore-forming material in the polyester fiber is removed to obtain an antistatic polyester fiber with conductivity and microporous structure.
[0048] The present application adds a conductive dispersion containing montmorillonite, polyaniline and polypyrrole when the esterification rate reaches 85% or more in the polyester synthesis stage, so that the blended materials can be embedded in the polyester chain, thereby effectively improving the conductivity and antistatic effect of the polyester fiber, and the effect has high stability and is not affected by the washing, dyeing and other treatments of the polyester fiber. At the same time, the embodiment of the present application adds pore-forming materials in the synthesis process of polyester and removes them after the polyester fiber is made, so that grooves or pores can be formed in the polyester fiber, increasing the specific surface area of the polyester fiber, which is more conducive to absorbing moisture and diffusing gas, thereby giving the polyester fiber better hygroscopicity and air permeability, and the improvement of the hygroscopicity of the polyester fiber can also further improve its antistatic effect.
[0049] Furthermore, in some embodiments, in step S1, the method for preparing the conductive additive comprises the following steps:
[0050] S11. The polypyrrole and the protonic acid are blended and dispersed in water, and then montmorillonite is added and stirred to obtain a montmorillonite dispersion;
[0051] S12. The polypyrrole and the oxidant are blended and dispersed in water to obtain a first mixed solution; the first mixed solution is added to the montmorillonite dispersion to obtain a second mixed solution;
[0052] S13. Adding the aniline suspension into the second mixed solution, after sufficient reaction, washing and drying the product to obtain the conductive additive.
[0053] Among them, the proton acid in the montmorillonite dispersion can pre-treat the montmorillonite so that polypyrrole is loaded on the surface of the montmorillonite; on this basis, the oxidant in the second mixed solution can be used to promote the aniline in the aniline suspension added later to generate polyaniline through chemical oxidation polymerization. At the same time, during the polymerization of aniline, the polypyrrole in the second mixed solution and the polyaniline generated by the reaction can enter the interlayer of the montmorillonite, increase the interlayer spacing of the montmorillonite, and improve the dispersibility of the montmorillonite in the polyester. On this basis, the conductive additive formed is added to the synthesis process of the polyester, which can effectively solve the problem of difficulty in uniform dispersion when polyaniline and polypyrrole are directly added, so that polyaniline and polypyrrole are uniformly dispersed in the polyester with the montmorillonite to form a continuous conductive network, which significantly improves the conductivity of the polyester. At the same time, the synergistic effect of polyaniline and polypyrrole not only enhances the electronic transmission ability of the material, but also improves its stability under different conditions. Moreover, the addition of montmorillonite can not only enhance the connectivity of the conductive network by improving the dispersibility of polyaniline and polypyrrole, but it can also reduce the resistance of polyester to a certain extent and improve the hygroscopicity and mechanical properties of polyester fibers. At the same time, the physical barrier effect of the interlayer space of montmorillonite can effectively inhibit the growth of bacteria and improve the antibacterial properties of polyester fibers.
[0054] Specifically, when preparing the conductive aid, the molar ratio of polypyrrole, montmorillonite, oxidant, and aniline protonic acid is 6:1:0.1~0.3:0.5:2; the mass ratio of polypyrrole used in step S11 and step S12 is 2:1; the aniline suspension used in step S13 is a suspension of aniline in water; the protonic acid includes at least one of hydrochloric acid, sulfuric acid, sulfosalicylic acid, and dodecylbenzenesulfonic acid, and the oxidant includes at least one of ammonium persulfate, potassium persulfate, ferric chloride, ferric sulfate, and ferric chloride.
[0055] The embodiment of the present application can adjust the ratio of each raw material to generate polyaniline through polymerization of aniline, and give full play to the synergistic effect between montmorillonite, polypyrrole and polyaniline to improve the performance of polyester fiber.
[0056] Furthermore, in some embodiments, in step S2, the mass fraction of the conductive auxiliary agent in the conductive dispersion is 25% to 35%.
[0057] In this embodiment, the conductive auxiliary agent can be fully dispersed in ethylene glycol, so as to be fully dispersed in the polyester during the synthesis process of the polyester.
[0058] Further, in some embodiments, in step S3, the step of synthesizing copolyester includes:
[0059] Mix terephthalic acid and ethylene glycol and carry out esterification reaction at 220-265°C;
[0060] Ethylene glycol is added to reduce the temperature, and then sodium bis(hydroxyethyl)isophthalate-5-sulfonate and the third monomer polyethylene glycol are added.
[0061] In this embodiment, by first adding ethylene glycol to cool down, it is possible to prevent sodium bis(hydroxyethyl)isophthalate-5-sulfonate from self-polymerization due to high temperature; the sodium bis(hydroxyethyl)isophthalate-5-sulfonate introduced in this embodiment can graft hydrophilic sulfonic acid groups into the polyester molecular chain to increase the moisture absorption rate of the fiber. Among them, the amount of ethylene glycol added for cooling accounts for 15% of the mass of terephthalic acid, the amount of sodium bis(hydroxyethyl)isophthalate-5-sulfonate added accounts for 10% to 20% of the mass of terephthalic acid, and the amount of polyethylene glycol added as the third monomer accounts for 10% to 25% of the mass of terephthalic acid.
[0062] More specifically, in the process of esterification, in order to prevent the generation of a large amount of diethylene glycol, an acyl inhibitor calcium acetate is also added. The pore-forming material is added in the polycondensation stage, specifically, the pore-forming material is added half an hour after the addition of the conductive dispersion. Nitrogen is introduced in the polycondensation stage. When the temperature is raised to 270°C, a low vacuum is drawn and the cooling point is controlled at 285°C. When the stirring power reaches a predetermined value, it means that the product reaches a predetermined viscosity, that is, the synthesis of the polyester is completed. At this time, the stirring and vacuum are stopped, and the nitrogen is pressed to discharge the material to obtain the polyester product.
[0063] Furthermore, in some embodiments, the mass of the conductive dispersion added in step S3 accounts for 10% to 20% of the mass of the terephthalic acid. The mass of the pore-forming material added in step S3 accounts for 8% to 15% of the mass of the terephthalic acid; and the pore-forming material includes at least one of calcium carbonate and sodium chloride.
[0064] In the above embodiments, by controlling the amount of conductive dispersion added and the proportion of pore-forming material, the proportion of conductive additive and the proportion of microporous structure in the polyester fiber can be effectively regulated, so that polyester fibers with excellent conductivity, moisture absorption, antistatic effect and mechanical properties can be obtained at a relatively low cost to meet the needs of practical applications.
[0065] Further, in some embodiments, in step S4, the step of removing the pore-forming material comprises:
[0066] The polyester fiber is immersed in a solvent, and the polyester fiber is taken out after the pore-forming material is fully dissolved; the solvent is a solvent that can dissolve the pore-forming material, and is preferably water or an acidic solution.
[0067] In this embodiment, by removing the pore-forming material, microporous structures such as grooves or small holes can be formed in the polyester fiber, thereby improving the moisture absorption and air permeability of the polyester fiber.
[0068] The antistatic polyester prepared by the above method has relatively stable conductivity and microporous structure, and its water absorption performance is comparable to that of natural fiber boxes. Textiles made from this polyester fiber have the characteristics of being dry and natural when in contact with the skin, and have excellent performance in moisture absorption, breathability and conductivity, and have excellent fluffiness and drape, which can effectively improve wearing comfort.
[0069] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0070] Example 1
[0071] This embodiment provides a method for preparing an antistatic polyester fiber having conductivity and a microporous structure, comprising the following steps:
[0072] S1. Preparation of conductive additives
[0073] 6 mol of polypyrrole (purity 98%, average Mw = 67.09) was divided into two parts for treatment. First, 4 mol of polypyrrole was mixed with 1 mol of protonic acid (dodecylbenzene sulfonic acid) and dispersed in 100 mL of deionized water. Then, 0.2 mol of montmorillonite (specific surface area 240 m 2 ·g -1 , pH value is 5.5), fully stirred to obtain a montmorillonite dispersion; 2 mol of polypyrrole and 0.5 mol of oxidant (ammonium persulfate) are blended and dispersed in 100 mL of deionized water to obtain a first mixed solution; the first mixed solution is added to the montmorillonite dispersion to obtain a second mixed solution; 2 mol of aniline is dispersed in 50 mL of deionized water to obtain an aniline suspension; the aniline suspension is slowly added dropwise to the second mixed solution, and after fully reacting for 6 hours under nitrogen protection, ultrasonic dispersion is performed in water, and then centrifugal separation is performed, and the obtained precipitate is washed with deionized water and then dried in a vacuum oven at 60° C. to obtain the conductive additive.
[0074] S2. Dispersing the conductive auxiliary agent in ethylene glycol to obtain a conductive dispersion liquid, wherein the mass fraction of the conductive auxiliary agent is 32.5%.
[0075] S3. adopt direct esterification method to synthesize copolyester: after 200g terephthalic acid and 90g ethylene glycol are mixed, add into the reactor with agitator, pressurize and discharge the water generated by esterification at 260 ℃, ensure the smooth progress of reaction, generate ethylene terephthalate. During, in order to prevent the generation of a large amount of diethylene glycol, a small amount of acyl inhibitor (calcium acetate) is also added. Then, add 30g ethylene glycol to cool the material, add 30 phthalic acid bis (hydroxyethyl) ester-5-sodium sulfonate and 30g third monomer polyethylene glycol, when the esterification rate reaches more than 85%, add 30g of conductive dispersion liquid, after half an hour interval, enter the polycondensation stage, pass nitrogen, and add 25g pore-forming material (calcium carbonate), when the temperature reaction reaches 270 ℃, draw low vacuum and control the temperature drop point at 285 ℃, after the product reaches the predetermined viscosity, namely complete the synthesis of polyester, stop stirring and vacuum at this moment, press nitrogen discharging, obtain polyester product.
[0076] S4. The polyester product is made into polyester fiber by a melt spinning process, and the polyester fiber is immersed in an acid solution to remove the pore-forming material in the polyester fiber to obtain an antistatic polyester fiber with conductivity and a microporous structure.
[0077] The SEM image of the antistatic polyester fiber with conductivity and microporous structure prepared in this embodiment is as follows: Figure 1 As shown by Figure 1 It can be seen that there are some grooves and small holes on the fiber surface, which is beneficial to improving the moisture absorption and air permeability of polyester fiber.
[0078] The conductive property, antistatic property and mechanical property of the antistatic polyester fiber with conductivity and microporous structure prepared in this embodiment were further tested. The results are shown in Table 1.
[0079] Table 1 Performance test results of polyester fibers prepared in Example 1
[0080] Volume resistivity Static half-life Tensile Strength <![CDATA[4.765×10 4 Ω·CM]]> 30s <![CDATA[2.36Cn·dteX -1 ]]>
[0081] It can be seen from Table 1 that the polyester fiber prepared in this embodiment has good conductivity, antistatic properties and mechanical properties, and can meet the needs of practical applications.
[0082] Comparative Example 1
[0083] This comparative example provides an antistatic polyester fiber with conductivity and microporous structure. Compared with Example 1, the only difference is that the preparation method of the conductive additive in step S1 is changed, and the other steps are consistent with Example 1, which will not be repeated here. In this comparative example, montmorillonite, polyaniline and polypyrrole are directly mixed as a conductive additive, and the amounts of montmorillonite, polyaniline and polypyrrole in the conductive additive are consistent with those in Example 1.
[0084] The conductive property, antistatic property and mechanical property of the polyester fiber prepared in this comparative example were tested, and the results are shown in Table 2.
[0085] Table 2 Performance test results of polyester fiber prepared in Comparative Example 1
[0086] Volume resistivity Static half-life Tensile Strength <![CDATA[7.844×10 7 Ω·CM]]> 40s <![CDATA[2.38Cn·dteX -1 ]]>
[0087] It can be seen from Table 2 that the polyester fiber prepared by directly mixing montmorillonite, polyaniline and polypyrrole as conductive additives exhibits significantly increased volume resistivity, slightly increased electrostatic half-life and enhanced tensile strength, and the overall antistatic effect is not ideal.
[0088] Comparative Examples 2-3
[0089] Comparative Examples 2 to 3 respectively provide an antistatic polyester fiber with conductivity and microporous structure. Compared with Example 1, the only difference is that the type of raw materials in the conductive additive in step S1 is changed, and the remaining steps are consistent with Example 1 and are not repeated here.
[0090] In Comparative Example 2, the conductive aid does not contain polyaniline, and the aniline in the aniline suspension is replaced by an equal amount of pyrrole, and the other steps are consistent with Example 1; in Comparative Example 3, the conductive aid does not contain polypyrrole, and polypyrrole is replaced by an equal amount of polyaniline, and the other steps are consistent with Example 1.
[0091] The conductivity, antistatic properties and mechanical properties of the polyester fibers prepared in Comparative Examples 2 to 3 are shown in Table 3.
[0092] Table 3 Performance test results of polyester fibers prepared in Comparative Examples 2 to 3
[0093] Comparative Example Volume resistivity Static half-life Tensile Strength Comparative Example 2 <![CDATA[4.913×10 9 Ω·CM]]> 54s <![CDATA[2.02Cn·dteX -1 ]]> Comparative Example 3 <![CDATA[5.432×10 4 Ω·CM]]> 120s <![CDATA[2.26Cn·dteX -1 ]]>
[0094] It can be seen from Table 3 that, compared with Example 1, when aniline is replaced by an equal amount of pyrrole, the volume resistivity of the material increases significantly to 4.913×10 9 Ω·CM, which indicates that the antistatic effect of the prepared material has not been significantly improved. On the contrary, when polypyrrole is replaced by an equal amount of polyaniline, the volume resistivity of the material increases slightly, with a specific value of 5.432×10 4 Ω·CM, but the static half-life of the material is extended to 120 seconds, the duration of the antistatic effect is too long, and at the same time, the tensile strength is reduced to 1.22Cn·dteX -1 , which is prone to breakage in practical applications, thus having an adverse effect on application performance.
[0095] Examples 2-3 and Comparative Examples 4-5
[0096] Examples 2 to 3 and comparative examples 4 to 5 respectively provide an antistatic polyester fiber with conductivity and microporous structure. Compared with Example 1, the only difference is that the proportion of each raw material used in preparing the conductive additive in step S1 is changed. The remaining steps are consistent with Example 1 and are not repeated here.
[0097] Table 4 shows the molar ratios of the raw materials used in preparing the conductive additives in Examples 2 to 3 and Comparative Examples 4 to 5.
[0098] Table 4 Molar ratio of each raw material when preparing conductive additives in Examples 2 to 3 and Comparative Examples 4 to 5
[0099]
[0100]
[0101] The conductivity, antistatic properties and mechanical properties of the polyester fibers obtained in Examples 2 to 3 and Comparative Examples 4 to 5 are shown in Table 5.
[0102] Table 5 Performance test results of polyester fibers prepared in Examples 2-3 and Comparative Examples 4-5
[0103] Comparative Example Volume resistivity Static half-life Tensile Strength Example 2 <![CDATA[3.08×10 8 Ω·CM]]> 56s <![CDATA[2.18Cn·dteX -1 ]]> Example 3 <![CDATA[5.012×10 5 Ω·CM]]> 28s <![CDATA[1.39Cn·dteX -1 ]]> Comparative Example 4 <![CDATA[6.113×10 6 Ω·CM]]> 118s <![CDATA[1.38Cn·dteX -1 ]]> Comparative Example 5 <![CDATA[2.154×10 8 Ω·CM]]> 67s <![CDATA[2.01Cn·dteX -1 ]]>
[0104] As can be seen from Table 5, compared with Example 1, Examples 2 to 3 change the amount of montmorillonite, wherein the amount of montmorillonite in Example 2 is reduced, resulting in a significant increase in both the volume resistivity and the electrostatic half-life. In Example 3, the amount of montmorillonite is increased, and although the electrostatic half-life is slightly reduced, the volume resistivity is increased, and the tensile strength is significantly reduced. This may be because excessive montmorillonite causes the internal structure of the fiber to become uneven, thereby affecting the mechanical properties of the fiber, which is not conducive to the smooth progress of the spinning process. Compared with Example 1, Comparative Examples 4 to 5 change the ratio of polypyrrole and aniline, which all lead to an increase in volume resistivity and electrostatic half-life, and a decrease in tensile strength, indicating that polypyrrole and aniline need to be in a specific ratio to enable the polyester fiber to exhibit better comprehensive properties. Therefore, in order to obtain a composite material with both excellent conductivity and good mechanical properties, it is preferred to prepare a conductive additive according to the method in Example 1 by using polypyrrole, protonic acid, montmorillonite, oxidant and aniline in a molar ratio of 6:1:0.2:0.5:2. This formula not only ensures that the material has a low volume resistivity and a short electrostatic half-life, but also maintains a high tensile strength, achieving a good balance between conductivity and mechanical properties to meet the needs of practical applications.
[0105] In summary, the present application provides an antistatic polyester fiber with conductivity and microporous structure and a preparation method thereof, which belongs to the field of polyester fiber. The present application prepares a conductive auxiliary agent containing montmorillonite, polyaniline and polypyrrole, and disperses the conductive auxiliary agent in ethylene glycol to obtain a conductive dispersion; then a direct esterification method is used to synthesize copolyester, and when the esterification rate reaches more than 85%, a conductive dispersion is added, and then a pore-forming material is added, and after the polycondensation reaction is completed, a polyester product is obtained; then a spinning process is used to make the polyester product into polyester fiber, and the pore-forming material in the polyester fiber is removed to obtain an antistatic polyester fiber with conductivity and a microporous structure. In the above manner, the present application can make montmorillonite, polyaniline and polypyrrole blended and embedded in the polyester chain, effectively improve the conductivity and hygroscopicity of the polyester fiber, and make it have a stable antistatic effect to meet the needs of practical applications.
[0106] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing an antistatic polyester fiber having conductivity and microporous structure, characterized in that: The steps include: S1. preparing a conductive additive comprising montmorillonite, polyaniline and polypyrrole; S2. dispersing the conductive aid in ethylene glycol to obtain a conductive dispersion; S3. Synthesizing the copolyester by direct esterification, adding the conductive dispersion when the esterification rate reaches 85% or more, and then adding the pore-forming material, and after the polycondensation reaction is completed, obtaining a polyester product; S4. The polyester product is made into polyester fiber by melt spinning technology, and the pore-forming material in the polyester fiber is removed to obtain an antistatic polyester fiber with conductivity and microporous structure.
2. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 1, characterized in that: In step S1, the method for preparing the conductive additive comprises the following steps: S11. The polypyrrole and the protonic acid are blended and dispersed in water, and then montmorillonite is added and stirred to obtain a montmorillonite dispersion; S12. The polypyrrole and the oxidant are blended and dispersed in water to obtain a first mixed solution; the first mixed solution is added to the montmorillonite dispersion to obtain a second mixed solution; S13. Adding the aniline suspension into the second mixed solution, after sufficient reaction, washing and drying the product to obtain the conductive additive.
3. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 2, characterized in that: In the process of preparing the conductive auxiliary agent, the molar ratio of polypyrrole, protonic acid, montmorillonite, oxidant and aniline is 6:1:0.1-0.3:0.5:2; the mass ratio of polypyrrole used in step S11 and step S12 is 2:
1.
4. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 2, characterized in that: The protonic acid includes at least one of hydrochloric acid, sulfuric acid, sulfosalicylic acid, and dodecylbenzenesulfonic acid, and the oxidant includes at least one of ammonium persulfate, potassium persulfate, ferric chloride, ferric sulfate, and ferric chloride.
5. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 1, characterized in that: In the conductive dispersion, the mass fraction of the conductive auxiliary agent is 25% to 35%.
6. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 1, characterized in that: The steps of synthesizing the copolyester include: Mix terephthalic acid and ethylene glycol and carry out esterification reaction at 220-265°C; Ethylene glycol was added to reduce the temperature, and then sodium bis(hydroxyethyl)isophthalate-5-sulfonate and polyethylene glycol were added.
7. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 6, characterized in that: The mass of the conductive dispersion added in step S3 accounts for 10% to 20% of the mass of the terephthalic acid.
8. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 6, characterized in that: The mass of the pore-forming material added in step S3 accounts for 8% to 15% of the mass of the terephthalic acid; the pore-forming material includes at least one of calcium carbonate and sodium chloride.
9. The method for preparing the antistatic polyester fiber with conductivity and microporous structure according to claim 8, characterized in that: In step S4, the step of removing the pore-forming material comprises: The polyester fiber is immersed in a solvent, and the polyester fiber is taken out after the pore-forming material is fully dissolved; the solvent is water or an acidic solution.
10. An antistatic polyester fiber with conductivity and microporous structure, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of antistatic copolyester
CN106380585A
Heavy-duty anticorrosive polyaniline coating and preparation method thereof
CN102634276A
Preparation method of in-situ polymeric composite conductive / antistatic fiber
CN107022805A
Preparation method of superfine porous hydrophilic polyester fiber
CN107653517A
Preparation method of antistatic wool-like polyester filament yarn
CN115559014A
Cited By
Moisture-absorbing and heating warm-keeping knitted fabric and preparation method thereof
CN120905800A